2020
DOI: 10.1021/acsami.0c09618
|View full text |Cite
|
Sign up to set email alerts
|

High-Fidelity Hydrogel Thin Films Processed from Deep Eutectic Solvents

Abstract: Polyampholyte (PA) hydrogels are a fascinating class of soft materials that can exhibit high toughness while retaining self-healing characteristics. This behavior results from the random distribution of oppositely charged monomers along the polymer chains that form transient bonds with a range of bond strengths. PAs can be dissolved in aqueous salt solutions and then re-cast via immersion precipitation, making them particularly useful as surface coatings in biomedical applications. Moreover, this immersion pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…In recent years, eutectic gels, also known as eutectogels, prepared by using deep eutectic solvent (DES) as the disperser, were proposed as an additional type of gel. , A DES is usually composed of a hydrogen bond acceptor (HBA) and a hydrogen bond donor (HBD), which has physicochemical properties, such as ionic conductivity and nonvolatility, similar to ILs. What is more, compared with ILs, the DES is nontoxic, biocompatible, and easily available . Thus, the use of DES has opened a window toward creating soft materials to meet the increasing demand for the sensing material in broad environments. , More recently, it has been demonstrated that conductive eutectogels can be used to assemble stretchable strain sensors, which attract much interest in wearable electronic devices. , …”
Section: Introductionmentioning
confidence: 99%
“…In recent years, eutectic gels, also known as eutectogels, prepared by using deep eutectic solvent (DES) as the disperser, were proposed as an additional type of gel. , A DES is usually composed of a hydrogen bond acceptor (HBA) and a hydrogen bond donor (HBD), which has physicochemical properties, such as ionic conductivity and nonvolatility, similar to ILs. What is more, compared with ILs, the DES is nontoxic, biocompatible, and easily available . Thus, the use of DES has opened a window toward creating soft materials to meet the increasing demand for the sensing material in broad environments. , More recently, it has been demonstrated that conductive eutectogels can be used to assemble stretchable strain sensors, which attract much interest in wearable electronic devices. , …”
Section: Introductionmentioning
confidence: 99%
“…The evaporation of water during processing not only reduces the solvent content but also increases the salt and PEC concentration in the solution, and alters the microstructure of the PEC and its properties . When the loss of water reaches a critical level, crystallization of the salt can occur, adversely affecting the uniformity and physical properties of the PEC . Therefore, a noncrystallizing and low-volatility solvent is needed.…”
mentioning
confidence: 99%
“…In terms of the phase diagram shown in Figure , a homogeneous material is obtained in the entire composition range apart from the two-phase region in the lower-left portion of the phase diagram, whereas KBr crystallization is observed at high salt concentrations in the corresponding ternary phase diagram for the PEC/water/KBr system. Similar behavior has been reported in a polyampholyte system, where the anionic and cationic charges reside on the same polymer component . In the EG/GudnSCN system, crystallization of the GudnSCN salt is prevented by its formation of a eutectic with ethylene glycol, which remains present in the system for long times because of its low volatility.…”
mentioning
confidence: 99%
See 2 more Smart Citations